Investigation of the relationship between prolactin and infertility by expression levels of kisspeptin (KISS1), KISS1 receptor, neurokinin (NK), NK receptor genes - Akbal, Eylül; Yılmaz, Mehmet Bertan (The European Research Journal, 2025)
Objectives: Prolactin level, which rises in the blood during pregnancy and after birth, plays a role in physiological events such as metabolism and reproduction. Increased blood levels of prolactin lead to various disorders. The most important of these are amenorrhea/galactorrhea and disruption of ovulation. Disruption of ovulation is a serious problem and can lead to infertility problems. Kisspeptin (KISS1) and Neurokinins are involved in the control of ovulation. This study aimed to explain the relationship between Prolactin and infertility with the expression levels of KISS1, KISS1 Receptor (KISS1R), Neurokinin (NK), Neurokinin Receptor (NKR) genes. Methods: Fourty female Wistar Albino rats, 12-16 weeks old, were used in this study. Three groups were formed, 10 rats were in Group-1 as Control, 10 rats were in Group-2 given Saline, and 20 rats were in Group-3 given Metoclopramide (Metpamid, Sifar, Turkey). The raising effect of Metoclopramide on blood Prolactin levels leading to infertility was helpful to clarify the process in comparison with the other two groups not given Metoclopramide. Results: In Group-3 given Metoclopramide, the blood Prolactin levels were found to be significantly higher compared to Group-1 and Group-2 subjects that were not given this drug. Expression values of KISS1, KISS1R and NK, NKR genes were found to be significantly decreased in Group-3, where the Prolactin level increased, compared to the other two groups (P<0.001). Conclusions: In this study, it has been shown that the expression levels of Neuropeptide genes (KISS1, NK) are suppressed with the direct effect of hyperprolactinemia, thus decreasing the amount and functions of Neuropeptides. In our study it was concluded that the negative effects of prolactin elevation on reproduction may be mediated by neuropeptides.